Two new and two little-known species of the genus Axenyllodes Stach, 1949 from Russia and Kazakhstan - Babenko, Anatoly; Shveenkova, Yulia; Arbea, Javier I. (Zootaxa, 2025)
A review of the genus Axenyllodes in the fauna of the European part of Russia and Kazakhstan is conducted, two new species (A. chinki sp. nov. and A. potapovi sp. nov.) are described, and A. ghilarovi Martynova is redescribed based on the holotype and new material from the Volga region. Taxonomic notes are also given on two other species of the genus, A. bayeri (Kseneman) and A. echinatus Fjellberg, occurring in this region.